DAMPAK INTEGRASI TEKNOLOGI DIGITAL DAN LITERASI DIGITAL TERHADAP MOTIVASI BELAJAR SISWA DALAM MENYONGSONG ERA INDONESIA EMAS 2045 - Salim; Lubis, Muhammad Arif Fadhillah (Algebra : Jurnal Pendidikan, Sosial dan Sains, 2025)
Digital technology integration is applied by universities as a process of utilising technology which is a challenge for educational institutions in the industrial revolution 4.0 towards 5.0 and also a challenge for graduates to improve their individual abilities. Student learning motivation in the use of technology integration is an important reference that needs to be considered. The analysis method used in determining what affects student learning motivation is PLS-SEM. Sampling in this study through the Random Sampling method. This study aims to see the effect of digital technology integration on learning motivation. The subjects in the study were 142 students of STIKes Indah Medan. The results show that digital technology integration has a significant effect on learning motivation (30.9%), digital literacy has a significant effect on learning motivation (63.8%). With these findings, student learning motivation can be increased by increasing digital literacy in gathering information.